The Urgence of Digital Media Development Based on â€œMotion Graphicâ€ for Early Childhood - Nugraha, Dadan; Hartati, Sofia; Jalal, Fasli (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
This research is oriented to the urgency of developing digital media for early childhood with the aim of describing the types of digital media owned and needed by schools such as digibooks, coloring applications, interactive videos, storytelling applications; and interactive game applications (a combination of digibooks, coloring, interactive videos and storytelling), as well as digital media owned and needed by schools for developmental aspects such as religious and moral values, cognitive, physical motoric, language and socio-emotional early childhood. This study uses a qualitative descriptive method with the research subject, namely educators and education staff at the PAUD level in West Java Province. The results of the study include 1) the type of digital media for early childhood that is most widely owned by schools, namely interactive video types (53.1%); 2) the types of digital media for early childhood that are most needed by schools are types of interactive game applications, namely a combination of digibooks, coloring, interactive videos and storytelling (67.4%); 3) Digital media owned by schools for aspects of language development (61.7%); 4) Digital media needed by schools for aspects of socio-emotional development (71.8%).